AMF COPING STRESS PADA IBU RUMAH TANGGA - Alnisa Min Fadlillah; Renny Husniati (LPPM Universitas Abdurrab, 2021)
This service activity is motivated by many problems that occur in housewives, especially housewives who do not work and young mothers who just had a child. Often, many of them felt bored and complain that their task is never end. As a result, housewives experience stress to depression. This has a negative impact on the mother's physical and mental health and can be affect to their relationships with spouses and childcare. Therefore, this activity aims to educate housewives about the importance of managing stress from an early age. The target of this service is housewives, parents of students at MI Raudhatul Athfal, Limo District, Depok. Several methods were used in this activity, including lecture, evaluation and question and answer, and counseling methods. In general, the enthusiasm of the participants was seen in this activity.